Molecular Phylogenetics of Alpinia (Zingiberaceae) in Peninsular Malaysia / Natasha Binti Jamil - Jamil, Natasha (2014)

(untitled)
72 taxa of the genus Alpinia from Peninsular Malaysia representing section Alpinia and section Allughas (Smith, 1990) were collected and sequenced with two primers namely nuclear ribosomal DNA of internal transcribed spacer region (ITS) and partial chloroplast maturase K gene (matK) gene. Both ITS and matK trees in this study reaffirm the polyphyletic nature of the Alpinia species and revealed that the grouping of the Alpinia species from Peninsular Malaysia reflects some degree of similarity with that of Rangsiruji et al. 2000b and Kress’s et al. 2005 phylogeny, and in most part, incongruent with Smith’s 1990 infrageneric classification. This study reaffirms that A. oxymitra is closely related to either Clade IV (the Zerumbet clade) or Clade V (the Eubractea clade) of Kress et al. 2005 phylogeny. Based on morphology and the phylogenetic trees, newly described A. suriana is closely related with A. rafflesiana, thus suggests possible hybridisation between A. rafflesiana and A.javanica. In addition, it is clear from the internal transcribed spacer (ITS) and maturase K (matK) phylogenetic results in this study that the Rafflesiana clade (represented by subclade VIa and subclade VIb -Fig. 3.3 and Fig. 3.4) is distinct as the species that belong to the section Allughas subsection Allughas sensu Smith (1990) formed a natural grouping; comprising only of the Peninsular Malaysian Alpinia species. Interestingly, A. scabra (section Alpinia subsection Presleia, Smith 1990) is a sister taxa to the Rafflesiana clade, strongly supported by the molecular analyses of both ITS and matK consensus trees. However, relationship of some Alpinia species from the ITS data within the Rafflesiana clade varies from that obtained from matK data. Incongruence among the ITS and matK data suggests possible hybridisation or introgression between closely related species or the species may have shared ancestral polymorphisms.